Improving The Effectiveness Of Teaching Social Innovation Through Social Learning Model Inquri In Class Vi Sdn 12 Jurai Limes Tower District Iv Academic Year 2013/2014 - Jafni Rianson (Jurnal Ilmiah Pendidikan Scholastic, 2017)
From the scope according to the teaching function of the Social Sciences seems clear concept (Expanding Communnity Approach) which starts from the things nearest to the students (families) to the further (global). The fact that the case is still much do teachers in the field, a learning process that dominates without regard to the basic ability of students, (Teacher Contered) without involving students actively in it . In general problem in this research is the extent to which the effectiveness of the inquiry model of ' social' can improve learning outcomes of students in the Social Sciences in the sixth grade at SDN 12 Jurai Limes Tower District IV District, the South Coast, in the academic year 2013/2014? This type of research is classroom action research (classroom action research), which has the ultimate objective is to improve the quality of learning in schools, educational relevance, quality of the education, education management efficiency. The research location is in the sixth grade at SDN 12 Limes Tower District IV Jurai, South Coastal District , the school year 2013/2014 . research subjects are students of class VI SDN 12 Limes Tower , Genab the semester, academic year 2013/2014. The final goal of teaching social studies is the formation of the learner as an intelligent social actors (Socially Intelligent Actor) which is formed from a touch of pedagogy . Based on the research showed an increase in the quality of students in the sixth grade value SDN No. 12 Limes Tower, in the academic year 2013/2014, the graph continues to rise, excellent 61%, good 9.5% and quite 23% and increased sense of solidarity between friends, group shows real changes that have an impact on everyday life including relationships with people such as interviews and visits. Of the overall activities carried out can be concluded that the model of the inquiry socially very suitable to be applied to examine the social phenomena that arise in the community, a fact primary school age children third grade had been able to carry out the stages of the inquiry by the hypothesis as the direction in problem solving and uses the fact as a hypothesis.